Easy Surgical Approach of the Posterolateral Corner of the Knee - Sylvain Guy MD; Fernando Cury Rezende MD, PhD; Alexandre Ferreira MD; Lamine Chadli MD; Alessandro Carrozzo MD; Thais Dutra Vieira MD; Bertrand Sonnery-Cottet MD (SAGE Publishing, 2021)
Background: The anatomy of the posterolateral corner (PLC) of the knee is complex. The approach of the PLC can be a challenging and stressful surgical time. Indications: The indications are posterolateral meniscal repair, open lateral meniscus allograft transplantation, posterolateral tibial plateau fracture, and PLC reconstruction for grade III sprains. Technique Description: The skin incision is straight, realized with the knee positioned at 90° of flexion, passing slightly posterior to the lateral epicondyle, anterior to the fibular head (FH), and ending on Gerdy's tubercle. The subcutaneous tissues are dissected posteriorly so as to expose the FH and the biceps femoris (BF) tendon. The aponeurosis of the peroneus muscles is incised vertically opposite to the anterior side of the FH. The common fibular nerve is exposed at the neck of the fibula. Metzenbaum scissors are then inserted subaponeurotically, posteriorly, and parallel to the BF tendon, superficially to the nerve. An incision is made opposite the scissor's blades, freeing the common fibular nerve. The BF tendon is spread forward and the lateral gastrocnemius is pulled posteriorly. Metzenbaum scissors are inserted in a closed position between the lateral gastrocnemius and the posterolateral joint capsule, and then spread to create a triangular door with a proximal base. The base consists of the BF tendon, the posterior side of the lateral gastrocnemius, and the anterior side of the posterolateral joint capsule. A counter-angled Hohmann retractor can now be applied against the posterior tibial plateau to retract the lateral gastrocnemius posteriorly and medially, exposing the PLC of the knee. Results: Noble structures are easily exposed and protected. The common fibular nerve is dissected and reclined posteriorly, and the popliteus vessels are reclined posteriorly and medially, protected by the lateral gastrocnemius. Passing under the BF tendon allows a better vision of the PLC along with less constraint than passing above, as the working window is further away from the femoral insertion of the lateral gastrocnemius. Discussion/Conclusion: The present surgical approach allows a simple, safe, and reproducible exposure of the PLC of the knee.